Socioeconomic determinants of alcohol consumption among non-Malays in Malaysia - Cheah, Yong Kang (Hitotsubashi University, 2015)
In light of the increases in prevalence of alcohol consumption, the objective of the present study is to examine the socioeconomic determinants of alcohol consumption in Malaysia.The Third National Health and Morbidity Survey (NHMS III) consisting of 13477 non-Malay respondents is used.The present study applies two logit models to analyse the factors affecting the likelihood of heavy and light alcohol drinking.The results show that the likelihood of heavy alcohol drinking is positively associated with younger individuals, lower income earners, males, the less-educated, non-singles, rural dwellers and the employed, whereas, the likelihood of light alcohol drinking is positively associated with higher income earners, the well educated, urban dwellers and the unemployed. Based on these findings, several policy implications are discussed.